Solusi Peningkatan Minat Wirausaha Dan Pengurangan Hambatan Minat Wirausaha Mahasiswa - Nimas Ayu Aang Uung Lestari; Siti Djamilah (PRAGMATIS, 2020)
The interest in entrepreneurship in Indonesia itself is still relatively low. This was evidenced by President Joko Widodo's conversation with members of the Indonesian HIPMI at the independent Palace, Jakarta, Thursday (5/4/2018). The president said that an average of 14% of the population of developed countries are entrepreneurs. "Almost every developed country, the standard has (population) entrepreneurs above 14%, while we still have 3.1%. This means that it needs acceleration. "So this needs to be followed up that there needs to be an increase in entrepreneurial actors in carrying out entrepreneurial activities. So, for this problems I need to submit this activity named Mawiha Wituwa (Mahasiswa Berwirausaha, Wirausaha untuk Mahasiswa ) in english called Student Entrepreneurship, Entrepreneur for Student. Mawiha Wituwa activities consist of learning soft skills and hard skills. In here Mawiha Wituwa wants to encourage students who are not interested in entrepreneurship by providing early education at the Faculty of Economics and Business. . This activity will give spirits for students in creating and innovating and motivating themselves to always excel in entrepreneurial activities